Prevalence of dental caries in preschool children: a cross-sectional study - Lauramaris de Arruda Regis ARANHA; Ângelo Esmael da Silva MAKLOUF; Luiz Augusto BELÉM JÚNIOR; Guilherme REGIS-ARANHA; Ângela Xavier MONTEIRO; Shirley Maria de Araújo PASSOS; Adriana Beatriz Silveira PINTO (Revista de Odontologia da UNESP)
Abstract Introduction According to a survey conducted by the Ministry of Health, more than half of Brazilian children have experienced dental caries at 5 years old. Objective This research aims to assess the ceo-d Index (decayed teeth, teeth with indicated extraction, and filled teeth) of schoolchildren enrolled in preschool in the public education system in the city of Barreirinha city, state of Amazonas. Material and method Cross-sectional study, with 279 preschoolers between 02 and 06 years old, from the public education system of the city of Barreirinha. Dental caries were assessed following the recommendations of the World Health Organization based on the criteria established for dental conditions. Result 279 preschoolers between 2 and 6 years old participated in the study. The prevalence of dental caries was 59.2%, the average ceo-d/CPO-D was 2.36 teeth, and the Significant Index of Dental Caries (Sic Index) was 5.72. Conclusion Preschool children show a high prevalence of dental caries and a high value of the decayed component (c), suggesting the need for health education and health promotion programs for preschool children in Barreirinha.